(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
The growth and adequate maturity of the agro-product are a function of the behavior of agricultural variables (e.g., pH, carbon, nitrogen) and environmental variables (e.g., air temperature, relative humidity, wind speed, and direction). In conditions where the crop takes place outdoors in a vicinity not close to the producer, such as sugar cane (Saccharum officinarum), monitoring these variables becomes complex. Based on this consideration, this article carries out an explanatory, descriptive study of the main agri-environmental variables, which must be considered for the design of a sugarcane monitoring system, which serves as a tool to support decision-making in the process of growing this poaceae. Timely knowledge of the behavior of the crop conditions will allow the cane grower to implement strategies that allow him to channel adequate crop development. Since, being the crop, a product to which its development is a function of the behavior of the agri-food variables, its monitoring becomes a factor of interest.